2018
DOI: 10.6000/1929-7092.2018.07.22
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Working Conditions and Employee Competences of Fresh Graduates on Job Expertise, Salary and Job Satisfaction

Abstract: This study explores the factors that have critical impacts on job expertise and further analyses on how the jobs affect salary and job satisfaction. Job seekers consider the working conditions when seeking jobs. However, he/she will acquire an ideal job or not, it depends on his/her employee competences. The former is his/her job demands and expectations and the latter is the ability he/she has. These two factors determine his/her job expertise which further influences the salary and job satisfaction. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
2
9
0
1
Order By: Relevance
“…Job satisfaction can be defined as the employee's subjective feelings towards how satisfied they are at the workplace based on their state of physical and psychological well-being (Hsiao & Lin, 2018). Indeed, job satisfaction is determined as a basic and principal factor that can be the main cause of performance, behavior, and staff reactions at the workplace (Hee et al, 2019).…”
Section: Career Commitment and Job Satisfactionmentioning
confidence: 99%
“…Job satisfaction can be defined as the employee's subjective feelings towards how satisfied they are at the workplace based on their state of physical and psychological well-being (Hsiao & Lin, 2018). Indeed, job satisfaction is determined as a basic and principal factor that can be the main cause of performance, behavior, and staff reactions at the workplace (Hee et al, 2019).…”
Section: Career Commitment and Job Satisfactionmentioning
confidence: 99%
“…A number of research results have proven the influence of competence on the performance of Setyaningtyas et al (2013) 2018), Rabo (2018), and Martini et al (2018). Based on this study, the following research hypotheses are presented: Hypothesis 1: Teacher competence has a significant positive effect on teacher performance According to Noe (in Hsiao & Lin, 2018); Goffin and Woycheshin (2006), competence is one's ability to do work based on knowledge, skills and work attitudes, and personality. Vindyani & Desiana's research results (Vindyani & Desiana, 2018) found that knowledge as one dimension of competence had a significant positive effect on work commitment.…”
Section: Teacher Competencementioning
confidence: 99%
“…Hypothesis 1: Work competence has a significant positive effect on work performance Noe (2009) (in Hsiao & Lin, 2018), defines the work competence of a person's ability to do his work with his skills, knowledge, attitudes, and personality. The same thing was stated by Goffin and Woycheshin (2006).…”
Section: Work Competencementioning
confidence: 99%